Control of Hematopoietic Stem and Progenitor Cell Function through Epigenetic Regulation of Energy Metabolism and Genome Integrity - Yang, Zhenhua (Stem Cell Reports, 2019)
It remains largely unclear how stem cells regulate bioenergetics and genome integrity to ensure tissue homeostasis. Here, our integrative gene analyses suggest that metabolic and genotoxic stresses may underlie the common functional defects of both fetal and adult hematopoietic stem and progenitor cells (HSPCs) upon loss of DPY30, an epigenetic modulator that facilitates H3K4 methylation. DPY30 directly regulates expression of several key glycolytic genes, and its loss in HSPCs critically impaired energy metabolism, including both glycolytic and mitochondrial pathways. We also found significant increase in DNA breaks as a result of impaired DNA repair upon DPY30 loss, and inhibition of DNA damage response partially rescued clonogenicity of the DPY30-deficient HSPCs. Moreover, CDK inhibitor p21 was upregulated in DPY30-deficient HSPCs, and p21 deletion alleviated their functional defect. These results demonstrate that epigenetic mechanisms by H3K4 methylation play a crucial role in HSPC function through control of energy metabolism and protecting genome integrity.